2022
DOI: 10.2196/38063
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Whole-Person Health and Resilience During the COVID-19 Pandemic and Beyond: A Cross-sectional and Descriptive Correlation Study

Abstract: Background The COVID-19 pandemic has prompted an interest in whole-person health and emotional well-being. Informatics solutions through user-friendly tools such as mobile health apps offer immense value. Prior research developed a consumer-facing app MyStrengths + MyHealth using Simplified Omaha System Terms (SOST) to assess whole-person health. The MyStrengths + MyHealth app assesses strengths, challenges, and needs (SCN) for 42 concepts across four domains (My Living, My Mind and Networks, My Bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(36 reference statements)
2
4
0
Order By: Relevance
“…The finding that there were inverse relationships between strengths and challenges/needs is consistent with previous MSMH studies, where concepts identified as strengths were less often identified as challenges and less likely to have needs, and vice versa (Agboola et al, 2022; R. R. R. R. Austin, Mathiason, Lu, et al, 2022;Rajamani et al, 2022). This aligns with the literature: healthy individuals with many strengths may not have as many challenges or needs;…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The finding that there were inverse relationships between strengths and challenges/needs is consistent with previous MSMH studies, where concepts identified as strengths were less often identified as challenges and less likely to have needs, and vice versa (Agboola et al, 2022; R. R. R. R. Austin, Mathiason, Lu, et al, 2022;Rajamani et al, 2022). This aligns with the literature: healthy individuals with many strengths may not have as many challenges or needs;…”
Section: Discussionsupporting
confidence: 90%
“…The level of PHN strengths exceeded that of all pre-vious samples reported in MSMH research (Agboola et al, 2022; R. R. R. R. Austin, Mathiason, Lu, et al, 2022;Rajamani et al, 2022). This aligns with literature noting the ability of PHNs to manage stressful situations through resilience factors and coping abilities (Kim et al, 2022;Monsen, Austin, Goparaju, et al, 2021;Nordstrom, 2022;Sierra-García et al, 2022).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations